جدید اُردو نظم پر عربی اثرات (اخترشیرانی، ن۔م راشد، منیرنیازی اور عبدالعزیز خالد کے خصوصی حوالہ سے) (Contemporary Journal of Social Science Review, 2025)
The influence of Arabic poetry and literature on modern Urdu poetry is an important but often overlooked area of literary research. Prominent modern poets such as Akhtar Shirani, N. M. Rashid, Munir Niazi, and Abdul Aziz Khalid have, either consciously or unconsciously, drawn upon the rich thematic and stylistic heritage of classical Arabic poetry. Their works reflect clear impressions of the Holy Qur'an, Hadith, Islamic history, and the broader Arabic literary tradition. In various poems, direct allusions or subtle translations of Qur'anic verses and Prophetic traditions (Ahadith) are evident, demonstrating the depth of their engagement with the spiritual and cultural atmosphere of the Arabic world.A close examination of their poetic diction reveals the frequent use of pure Arabic vocabulary, metaphors, and rhetorical techniques such as tashbih (simile) and istiara (metaphor), which are hallmarks of the classical Arabic style. These elements not only enrich the aesthetic quality of their poetry but also serve as a testament to their profound connection with the Arabic linguistic and cultural milieu. Furthermore, the thematic undertones of these poets often resonate with the spiritual, philosophical, and moral concerns found in classical Arabic poetry, thereby bridging the cultural and literary traditions of the Arab and South Asian worlds.This study highlights how these modern Urdu poets have maintained an enduring dialogue with Arabic literary and religious heritage, allowing the fragrance of Arab civilization to permeate their works and shape the identity of contemporary Urdu poetic expression.